Strategy on Product Uniqueness, Market Segmentation, and Diversity of Activities for Creating the Quality of Agrotourism Education in Kampoeng Kopi Banaran (Proceeding International Collaborative Conference on Multidisciplinary Science, 2024)
This study aims to conduct a study on how the offering of product diversity, the accuracy of market segmentation and various tourist activities in educational tourism in the Kampoeng Kopi Banaran area, Semarang Regency meet the criteria as a quality special interest tourism attraction. The research method uses qualitative research methods with in-depth interviews with informants, questionnaire, direct observation and document studies. The results of the study show that the uniqueness of Kampoeng Kopi Banaran products offers a unique experience in special interest tourism cluster of outdoor, sport and adventure, lifestyle and educational tourism, agrotourism coffee from cultivation to processing and accommodation in the middle of plantations. Market segmentation is dominated by the coffee lovers’, the education, the family and the business segment. The tour in Kampoeng Kopi Banaran meets the quality criteria of special interest tourism, which meets the aspects of rewarding, enriching, adventuring and learning for visitors.